The Organization(s) of Well-being and Productivity: (Re)assembling work in the Danish Post - Mette Mogensen (Copenhagen Business School (CBS), 2012)
The well-being of employees is currently a central matter of concern both in public and private companies. If employees do not feel well, in the last instance they might experience a burn out or fall ill from stress and thus add to the highly costly yet ever growing number filling up the statistics of this modern epidemic. In short, well-being is key to productivity. For sure this is not a new story, but at the core of organization and management theory: how to best organize the human resources of production balancing off the need for increased productivity and the preservation of physical and mental resources of the worker? In contrast to classic principles such as Taylor's scientific management, it seems today generally agreed that well-being thrives when work is organized by principles of `flexibility', `learning', `empowerment' and `creativity'. However, at the same time workplaces and organizations are under an enormous pressure towards standardization and optimization. This dissertation investigates empirically competing or intersecting ways of organizing well-being and productivity, with an analytic outset in the work task, departing from historically generated, however still prevalent, dichotomies and normativities of standardization and flexibility respectively. The empirical case of the dissertation is the organization of postal work in a big and formerly publicly run distribution company in Denmark. Based on an ethnographic field work and the employment of an auto-photographic method, the dissertation investigates how the current and simultaneous efforts of standardization and flexibility configure the well-being(s) and productivities of postal work. The theoretical framework is primarily informed by Actor Network Theory and the dissertation attend to a detailed investigation of how well-being and productivity are enacted in the daily work practices and the constant shifting/delegation going on between the inscribed postal worker of work tools, standard procedures and management programs on the one side and the routinized bodies of the postal workers on the other. Most of the time this results in `working compatibilities' silently enacting bodies-with-standards that are both productive and well. At other times, however, controversy and conflicts arise, pointing to the fact that the presence of multiple modes of organizing are not always productive. The empirical chapters departs from selected auto-photographs that prompt different unfoldings of the way postal work is organized – or sought organized – and the way well-being and productivity arise as effects of these organizations. In this unfolding the analysis proceed on a tension between phenomenological and actor-network theoretical readings of empirical material creating a patchwork-like assemblage of postal work. This involves a stitching together of highly mundane, corporeal practices and material such as bicycles and kickstands, personal experiences, the researcher's interpretations, the technical scripts of electric bikes, the norms of postal workers, the discourse of management and the political-economic developments of European postal markets. Through the empirical chapters, the dissertation depicts postal work not as a story of standardization versus flexibility, but as a constant `juggling' and balancing act between them. This is not a story of humanization or the opposite, it is both at once. It is not a story of stabilization or perpetual change, it is both at once. It is a story of the hanging-togetherness of an organization that displays multiple versions of well-being and productivity as well as multiple controversies as a result of this. Depending on the stakes one has in this complex organizational set-up, whether one is the postal worker, the local manager, the HR consultant or perhaps the customer, preferences will differ, and indeed this is an important discussion. What is the better way to organize postal work? The analysis presented in the dissertation will not deliver the answer to this, but hopefully make the discussion a more qualified one, by displacing old truths. Having as point of departure and final emphasis a heuristics of the work task, the thesis aims to contribute to a specification of organization theory, HRM and work environment theorizing, which otherwise tend to have lost its primary object: work.
hdl:10398/8589
Keywords: 650